PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TEMA 8 SUB TEMA 2 KELAS 4 SD N 1 GODONG 2022 - Renita; Choirul Huda; Prasena Arisyanto (STKIP Subang, 2022)
The purpose of this study was to determine the results of the application of the project based learning on the learning outcomes of students in theme 8 sub-theme 2 for grade 4 SD Negeri 1 Godong. This study uses a quantitative method, with a Pre-Experimental Design Group in the form of One-Group Prettest-Posttest Design. Data collection techniques in this study were through observation, interviews, tests consisting of prettest-posttest with data analysis techniques using paired sample t-test with db N1+N2-1 and a significant level of 0.05. The results showed that the average posttest 80.6. Based on the results of the paired sample T-test was obtained that Tcount= 4.532 and Ttable= 2.037. From the results of these calculations obtained Tcount > Ttable , it can be concluded that the application of the project based learning succeeded in improving the learning outcomes of 4th grade students of SD Negeri 1 Godong. Based on the results of the research obtained, the researcher suggests that the project based learning can be used as an alternative in schools to improve student learning outcomes.